Regional climate variability impacts on the annual grape yield in Mendoza, Argentina - Agosta, Eduardo (2011)
The Mendoza Province is the major Argentinian vitivinicultural region and its grape production is fundamental for the national vintage. 1979-2009 climate-annual grape yield relationships are analyzed. Total grape yield is shown to depend significantly on regional ´summer´ (October through March) precipitation. Precipitation negatively impacts yields through plant disease and damage/destruction by hail. At interannual scales, ´summer´ regional precipitation variability can explains 25% of the yield variance. Summer precipitation modulates yield with a 6-8 years period: wet (dry) summers can be associated with larger (smaller) grape damage/loss probability during the summer preceding the vintage, as well as lower (higher) grape yields in the subsequent annual campaign due to bud damage. When monthly mean precipitation in Mendoza Observatory is considered wetter Novembers/Decembers can lead to lower yields. Hail during the summer of the previous harvest and during December could lower yields. Winter, late spring and early summer mean maximum temperatures can impact current and subsequent annual yields: warmer (colder) months are linked to enhanced (decreased) yields. These relationships can be associated with circulation and SST conditions in the equatorial and extratropical Pacific basin and southern South America: SSTs within the southeastern South Pacific are related to western equatorial Pacific SSTs and convection, which modify circulation and water vapor transport over southern South America. Statistical multilinear modeling shows that the observed relationships between yield, precipitation and temperature can explain at least 60% of the observed interannual yield variability. It is thus possible to quantitatively estimate, some months in advance, the upcoming vintage´s yield.